THE ROLE OF THE INTERNATIONAL ACCOUNTING STANDARDS BOARD IN LEADING FINANCIAL ACCOUNTING: AN ANALYTICAL STUDY - Ass. Prof. Dr. Muna Kamel Hamad (Scholars Digest Publishing, 2025)
The intention of this study was to describe the growth of the leading role of the International Accounting Standards Board ) IASB) in financial accounting by framing its scope in scientific and practical terms. The aim was pursued with regard to historical development for the (IASB) that led to its establishment in 1973 and its management of the theoretical aspect of accounting against the backdrop of intellectual thought in accounting with respect to the framework setup by the American Accounting Standards Board ( AASB). In addition, the Board's management of the practical aspect of financial accounting through the trends and advances in the (IAS) that would influence the preparation of business statements to the year 2024 was traced. To carry out its work, the study adopted a comparative analytical technique. The study, however, arrived at sound conclusions, perhaps the most outstanding one being that, the International accounting harmonization is one tool of integration into the global economy, so there has been a global trend toward the existence of international accounting standards as a common cross-border business language that helps drive the global economy, International accounting and financial reporting standards are subject to periodic updates by the ) IASB) in response to changes in the economic environment, such as changes in business models or the emergence of new financial instruments. Thus, the Board plays a leading role in enhancing the integration between theory and application, as it combines advanced accounting theories and practical practices to meet the needs of global financial markets.
Keywords: International Accounting Standards Board, Theoretical Framework of Financial Accounting, Practical Framework of Financial Accounting.